ЈАЗИЦИТЕ ВО КОНТАКТ И НИВНОТО МЕЃУСЕБНО ВЛИЈАНИЕ НА ПЛАНОТ НА ЛЕКСИКАТА (ВРЗ ПРИМЕРИ ОД ЗАПАДНОПРЕСПНАСКИОТ ГОВОР) (Philological Studies, 2019)
In this article, most of our attention is devoted to the impact the Albanian language has with the creation of the Albanian national state, and the increased presence of the Albanian language element in the region of Mala Prespa where Macedonian population lives, whose speech is part of the Macedonian language known as West-Prespa’s speech in the science of languages. Our lexical description would go towards establishing a pan-Slavic vocabulary and the use of certain specific words (in terms of their specific meanings and usage), the presence of other lexical items in West-Prespa’s speech or the contact that the Macedonian population in the region of Mala Prespa has with other peoples and their mutual influence in the area of vocabulary.